Cost accounting in Cambodia’s garment industry: A case study - Flores, Edman; Lim, Siphat; Uy, Juliet (Edelweiss Applied Science and Technology, 2024)
This study examines the cost accounting practices of garment manufacturers in Cambodia, with a particular focus on a leading company in the industry. By conducting in-depth interviews and analyzing secondary data, such as cost breakdown reports and job costing sheets, the research provides valuable insights into how cost accounting influences production efficiency and sustainability. The findings indicate that the company utilizes a detailed job order costing system integrated with FOB costing principles, meticulously tracking direct material, direct labor, production overhead, and non-production costs. This comprehensive approach facilitates accurate cost determination and informed pricing decisions, thereby ensuring profitability. This study is the first to offer an in-depth examination of cost accounting practices in the Cambodian garment industry, providing a unique, contextualized understanding of the challenges and strategies of a leading garment manufacturer in the country. However, the research is limited to a single case company, which may not fully represent the broader industry. Future research should consider comparative studies across multiple manufacturers to provide a more comprehensive understanding of industry practices.